HBM4EU-MOM: intervene to raise awareness to specific dietary recommendations and reduceprenatal mercury exposure - Namorado, Sónia (2022)
Abstract publicado em: Environ Health Perspect. 2021;1. https://ehp.niehs.nih.gov/doi/abs/10.1289/isee.2021.P-473